Efficacy and safety of Panax notoginseng saponin injection in the treatment of acute myocardial infarction: a systematic review and meta-analysis of randomized controlled trials - Chen, Pengfei; Gao, Zhuye; Guo, Ming; Pan, Deng; Zhang, He; Du, Jianpeng; Shi, Dazhuo (Frontiers in Pharmacology, 2024)
This study aimed to assess the efficacy and safety of Panax Notoginseng Saponins (PNS) injection, when combined with conventional treatment (CT), for acute myocardial infarction (AMI). Methods: Comprehensive searches were conducted in seven databases from inception until September 28, 2023. The search aimed to identify relevant randomized controlled trials (RCTs) focusing on PNS injection in the context of AMI. This meta-analysis adhered to the PRISMA 2020 guidelines, and its protocol was registered with PROSPERO (number:CRD42023480131). Result: Twenty RCTs involving 1881 patients were included. The meta-analysis revealed that PNS injection, used adjunctively with CT, significantly improved treatment outcomes compared to CT alone, as evidenced by: (1) Enhanced total effective rate [OR=3.09, P<0.05]. (2) Decreased incidence of major adverse cardiac events [OR=0.32, P<0.05]. (3) Reduction in myocardial infarct size [MD=-6.53, P<0.05]. (4) Lower ST segment elevation amplitude [MD=-0.48, P<0.05]. (5) Mitigated myocardial injury as indicated by decreased levels of creatine kinase isoenzymes [MD=-11.19, P<0.05], cardiac troponin T [MD=-3.01, P<0.05], and cardiac troponin I [MD=-10.72, P<0.05]. (6) Enhanced cardiac function, reflected in improved brain natriuretic peptide [MD=-91.57, P<0.05], left ventricular ejection fraction [MD=5.91, P<0.05], left ventricular end-diastolic dimension [MD=-3.08, P<0.05], and cardiac output [MD=0.53, P<0.05]. (7) Reduced inflammatory response, as shown by lower levels of c-reactive protein [MD=-2.99, P<0.05], tumor necrosis factor-α [MD=-6.47, P<0.05], interleukin-6 [MD=-24.46, P<0.05], and pentraxin-3 [MD=-2.26, P<0.05]. (8) Improved vascular endothelial function, demonstrated by decreased endothelin-1 [MD=-20.56, P<0.05] and increased nitric oxide [MD=1.33, P<0.05]. (9) Alleviated oxidative stress, evidenced by increased superoxide dismutase levels [MD=25.84, P<0.05]. (10) No significant difference in adverse events [OR=1.00, P=1.00].Conclusions: This study highlighted the efficacy and safety of adjunctive PNS injection in enhancing AMI patient outcomes beyond CT alone. Future RCTs need to solidify these findings through rigorous methods.